Trade, FDI and income inequality: empirical evidence from CIS. Issue 1 (28th February 2019) - Khan, Imran; Nawaz, Zuhaba
Abstract : Purpose: The purpose of this study is to examine the relationship between trade, foreign direct investment (FDI) and income inequality for Commonwealth of Independent States (CIS), using annual data from 1990 to 2016. The study attempts to answer a critical question: does openness affect income distribution? Design/methodology/approach: The analysis of the model involves the examination of likely non-linear effects of both trade and FDI on income distribution. Therefore, system-generalized method of moments (SYS-GMM) estimator was applied to mitigate the problem of non-linearity and possible endogeneity. In the second stage, the model was extended to test the impact of education on income inequality. The hypothesis is that secondary school enrollment speeds up the process of adoption of contemporary technology and decreases inequality. Findings: Trade and FDI have significant effects on income inequality when interacted with Gini-index; in case of trade, an inverted U-shaped curve holds as purposed by the trade theory. The components-wise effect of trade was held, except imports from advanced countries was found insignificant. Moreover, results were not found significant in case of human development index. Different results were found when trade and FDI interacted with education, which represents an important channel through which inequality is affected. Research limitations/implications: The study implies that CIS needs to re-design trade and FDI policies by encouraging trade and FDI inflows into industries and sectors aligned with structural adjustments, domestic industries uplift and investment in social infrastructure. Originality/value: This is the first study that has examined the impact of openness of income distribution in case of CIS.